A Study of Menstrual Problems Among the Female Junior College Students from Rural Area of Sangli District - Vivek B Waghachavare; Vishwajeet M Chavan; Girish B Dhumale (Medsci Publications, 2013)
Background: The various studies have found out significant amount of menstrual problems among adolescent girls. Some of the most common problems are dysmenorrhoes, premenstrual syndrome, abnormal uterine bleeding, amennorhoea, etc. The situation is especially worse in rural areas. These problems aggravate the psychological problems like depression. Objective: To study the menstrual problems, among female students of junior college students from rural area of Sangli District. Methodology: It was cross-sectional study conducted in randomly selected higher secondary college in rural area from Western Maharashtra, during September 2012 to October 2012. The calculated sample size for the study was 121. The sampling technique used was stratified ramdom sampling. A self administered questionnaire was used for data collection. Analysis was done using percentage and chi - square test. Results: Total 186 girl students participated in the study. Total 119 (64%) students were suffering from some menstrual problems. Dysmenorrhea was the commonest menstrual problem, and was present in 42.5% students. It was followed by weakness & giddiness during menstruation, menorrhagia, irregular menstruation etc. Primary amenorrhoea was present in 33 students. While 32 were suffering from premenstrual syndrome. Depression was present in 34.4% of students. Among those suffering from any menstrual problems only 43 (36.13 %) had consulted to doctor at some point of time. Conclusion: Menstrual Problems are present among majority of the adolescent girls, which highlights the need for proper professional counseling.